ANALISIS PENGARUH DEBT TO EQUITY RATIO (DER) TERHADAP PRICE TO BOOK VALUE (PBV) DENGAN RETURN ON EQUITY (ROE) SEBAGAI VARIABEL INTERVENING (Studi Kasus pada Perusahaan Indeks LQ45 yang Terdaftar di Bursa Efek Indonesia Tahun 2013-2016) - Marthalova, Rani Atika; Ngatno, Ngatno (Jurnal Ilmu Administrasi Bisnis, 2018)
This research aims to analyze the influence of debt to equity ratio (DER) towards price to book value (PBV) through return on equity (ROE) at index LQ45 companies listed on the Indonesian Stock Exchange (IDX) from 2013 to 2016. The population of this research is index LQ45 companies. Sampling method used in this research is purposive sampling that obtains 40 companies as sample. The research data analysis uses Regression test, path analysis and mediation test (Sobel test) by using program of SPSS 21. The result shows that ROE is able to mediate the influence of DER on PBV. This research proves that with the existence of ROE, then the addition of DER could increase PBV. Furthermore, to achieve ROE at index LQ45 companies, DER has to be further improved so that later will increase PBV.